2020
DOI: 10.1111/bjet.13024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an immersive virtual learning environment for operator training in mechanical and plant engineering using video analysis

Abstract: Her research interests are focused on reasonable applications of virtual reality in education, technology acceptance and the transfer of virtual learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…This factor was most often expressed by respondents as a pre-acquisition concern (I3, 4, 6, 9, 15). Howev-er, eight respondents indicated that appropriate calculations had been made in advance, showing that IVR would be profitable at the current time of the survey or in the future (I1, 2,5,8,9,11,14,15). Cost savings can be achieved through IVR, e.g., by saving travel expenses for visits or training, costs for expensive machines and equipment that do not have to be purchased separately or would stand still during training, and the possibility of being able to train faster and more flexibly.…”
Section: Implementation Of Ivr In the Surveyed Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This factor was most often expressed by respondents as a pre-acquisition concern (I3, 4, 6, 9, 15). Howev-er, eight respondents indicated that appropriate calculations had been made in advance, showing that IVR would be profitable at the current time of the survey or in the future (I1, 2,5,8,9,11,14,15). Cost savings can be achieved through IVR, e.g., by saving travel expenses for visits or training, costs for expensive machines and equipment that do not have to be purchased separately or would stand still during training, and the possibility of being able to train faster and more flexibly.…”
Section: Implementation Of Ivr In the Surveyed Organizationsmentioning
confidence: 99%
“…IVR currently includes various trackers, the HMD, and a PC or laptop. The connection of the individual components does not always work perfectly and can present challenges to inexperienced users as well as be time-consuming to use, depending on the number of systems (I1, 2,8,10,11,12). The participants asked for improved plug-and-play solutions that are less error-prone and easier to set up.…”
Section: Acceptance Factors Of Trainersmentioning
confidence: 99%
“…According to Abdullah et al (2021), technology-based learning tools can improve students' higher-order thinking skills. However, this can happen if students can use it as optimally as possible (Pletz & Zinn, 2020), because in fact, in this study the use of technology in immersive virtual learning was less than optimal in training students higherorder thinking skills and understanding climate change material. The technology used in immersive learning is not something that can improve learning outcomes universally, but only applies to certain fields (Beck, 2019) and if applied effectively (De Back et al, 2021).…”
Section: ▪ Results and Disscussionmentioning
confidence: 75%
“…Some work in the special section makes particular progress in terms of IVR research methodologies . Pletz and Zinn (2020) examined the degree of transfer between IVR training and real‐world machine operation tasks in the manufacturing sector using structured qualitative video analysis techniques. Their comprehensive coding approach, which focused on design, instruction, interaction, errors, difficulties and other anomalies enabled the research team to detect which actions the participants found most difficult.…”
Section: Overview Of Papersmentioning
confidence: 99%